2002
DOI: 10.1007/s10350-004-6425-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sphincter-Sacrificing Surgery for Rectal Carcinoma on Quality of Life in Muslim Patients

Abstract: Two aspects of religious worship (praying and fasting) were significantly impaired in the Muslim patients who had a stoma as a result of sphincter-sacrificing surgery. To improve quality of life in these patients, religious issues as they relate to the presence of a stoma should be discussed during preoperative counseling, the informed consent process, and counseling with local religious authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 21 publications
4
70
2
8
Order By: Relevance
“…All of these can influence how patients assess their QOL with a permanent colostomy. The study by Kuzu et al [32] which showed APR patients had worse QOL, included patients from a lower socioeconomic level. It is possible that these patients may have had problems managing their stoma due to lack of proper supportive care.…”
Section: Sphincter Preservation Versus Permanent Colostomymentioning
confidence: 98%
“…All of these can influence how patients assess their QOL with a permanent colostomy. The study by Kuzu et al [32] which showed APR patients had worse QOL, included patients from a lower socioeconomic level. It is possible that these patients may have had problems managing their stoma due to lack of proper supportive care.…”
Section: Sphincter Preservation Versus Permanent Colostomymentioning
confidence: 98%
“…Some studies have shown that persons with ostomies have worse HRQOL than their counterparts with anastamosis [4][5][6][7] ; other studies show similar or mixed HRQOL across…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Spouses with an active sex life prior to surgery were found to have inactive sex life after surgery, spouses with active sex life had decreased number of sexual intercourse, and majority of the couples did not have sexual relationship after stoma opening. 4,30,47 …”
Section: Stoma and Sexual Lifementioning
confidence: 99%